A Praise Poem of Warad-Sîn, King of Larsa, to Nippur - Földi, Zsombor J. (Altorientalische Forschungen, 2020)
This paper publishes a praise poem of Warad-Sîn, king of Larsa. The manuscript, a one-column tablet, comes from a private collection and is unprovenanced. The text might be an excerpt from a longer composition. Its 20 lines long text praises first Nippur, the city of Enlil, then Warad-Sîn speaks in the first person about the commission given to him by Enlil, about his deeds to the city, and about their permanence. The author of this text appears to be familiar both with the literary corpus and the royal inscriptions of the early Old Babylonian period.